(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2010)
In this contribution the author looks into Calvin’s understanding of self-denial. The author indicates that, although no longer in use in modern theology, self-denial can assist Christians to understand their relationship with God and fellow-persons better in view of self-denial. The author also identifies the positive value of self-denial for ethics and pastoral care. Calvin’s view on self-denial is outlined, explained and commented on. Calvin regards self-denial as to live in the presence of God, to accept his Will regardless what happens in life and to roll-out to fellow believers an attitude of care. This study uses abortion and mercy killing (as examples in ethics) and suffering (as example in pastoral care) to contextualize the applicability of self-denial for every day life. The study concludes with a positive appreciation of self-denial and links this in various ways to the relationship between God and fellow-persons.